Du Finis Hispaniae à l’Espagne du Plus Ultra, l’hispano-américanisme comme instrument de régénération nationale - David Marcilhacy (Cahiers de Civilisation Espagnole Contemporaine)
Appeared at the time of the collapse of the ultramarine Spanish empire, symbolized by the Finis Hispaniae launched in 1895 by Chamberlain, the Spanish-Americanist current arises within regenerationism as one of the most coherent discourse to modernize Spain, opening it to America while renewing itself with a discourse enhancing its past and its collective identity. Between the openly liberal and pragmatic reformist program carried by Rafael Altamira as early as the beginning of the century, and the manifestations of the official Americanism that prevailed under the dictatorship of Primo de Rivera - symbolized by the transatlantic flight of the Plus Ultra seaplane or by the Ibero-American Exhibition - the trajectory of Spanish Americanism reflects the ambiguities of a nation in search of international recognition and torn by an impossible consensus on the ways of its modernization.